The effect of sequential perioperative intravenous tranexamic acid in reducing postoperative blood loss and hidden blood loss after posterior lumbar interbody fusion: a randomized controlled trial - Dong, Wei; Liang, Yi; Li, Dongxu; Ma, Zhaoxin; Cheng, Minghuang; Zhang, Xiaojun; Shen, Jieliang; Zhou, Nian; Hao, Jie; Jiang, Wei; Hu, Zhenming (Frontiers in Medicine, 2023)
Background Tranexamic acid (TXA) has previously been shown to be effective in reducing intraoperative blood loss (IBL) and transfusion requirements in spine surgery. A conventional TXA regimen is a simple preoperative or intraoperative administration. However, the hyperfibrinolysis caused by surgical trauma lasts at least 24 h, and a single dose of TXA cannot cover the whole process of hyperfibrinolysis. Moreover, its ability to control postoperative blood loss (PBL) may be insufficient. Therefore, this study aimed to explore the effects and safety of sequential perioperative intravenous TXA for reducing bleeding after posterior lumbar interbody fusion (PLIF). Methods Patients requiring PLIF were randomly divided into two groups. All patients were intravenously injected with 1 g of TXA 15 min before skin resection. Every day after the surgery, 200 ml saline was intravenously injected for 1–3 days in Group A, while Group B received 1 g of TXA instead of saline. The total blood loss (TBL), IBL, PBL, HCT, Hb, blood transfusion volume, inflammation-related indicators, and complications were recorded. Results TBL, PBL, and hidden blood loss (HBL) in Group B were significantly lower than those in Group A (P < 0.05). The maximum decreases in HCT and Hb in Group B were also significantly lower than those in Group A (P < 0.05), and the drainage removal time (DRT) was sooner in Group B than in Group A (P = 0.003). On the 3rd and 5th days after surgery, the level of CRP in Group B was significantly lower than that in Group A (P < 0.05). Similarly, IL-6 levels were significantly lower in Group B for the first 5 days postoperatively (P < 0.001). Sex, operation time, level of decompression, length of incision, and change in HCT were significant predictors of both TBL and HBL. TBL was also significantly associated with BMI and preoperative fibrinogen, while postoperative TXA was a significant predictor of HBL only. Conclusion Intravenous injection of 1 g of TXA 15 min before skin resection combined with continuous intravenous injection of 1 g of TXA 1 to 3 days after PLIF can reduce postoperative bleeding and shorten the time to drainage tube removal. In addition, it can also inhibit the postoperative inflammatory response. Clinical trial registration ChiCTR2200056210.